Folding behavior of four silks of giant honey bee reflects the evolutionary conservation of aculeate silk proteins - Jakkrawut Maitip (2018)
© 2015 Elsevier Ltd. Multiple gene duplication events in the precursor of the Aculeata (bees, ants, hornets) gave rise to four silk genes. Whilst these homologs encode proteins with similar amino acid composition and coiled coil structure, the retention of all four homologs implies they each are important. In this study we identified, produced and characterized the four silk proteins from Apis dorsata, the giant Asian honeybee. The proteins were readily purified, allowing us to investigate the folding behavior of solutions of individual proteins in comparison to mixtures of all four proteins at concentrations where they assemble into their native coiled coil structure. In contrast to solutions of any one protein type, solutions of a mixture of the four proteins formed coiled coils that were stable against dilution and detergent denaturation. The results are consistent with the formation of a heteromeric coiled coil protein complex. The mechanism of silk protein coiled coil formation and evolution is discussed in light of these results.